Analisis Model Kanal SUI Berdasarkan Modulasi QAM dan Variasi Bandwidth - Frans Sugiharto; Imam Santoso; Ajub Ajulian Zahra (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Wimax is the wireless technology providing link of broadband in distance which far. Wimax is technology of broadband having high speed access and the wide reach. Such as system communications of previous nirkabel, wimax also have model of different propagation. Propagation models of wimax involve variation of delay (μs), power (dB), Factor K (dB), Doppler frequency (Hz). This Model called SUI (Stanford University Interim) channel. Variation of Parameters SUI channel determine performance of communications wimax. In this final project, analysed SUI channel use simulation where parameter of SUI channel of variation into 6 condition of channel SUI - 1 up to SUI-6. While performance of channel presented in comparison of graph of BER and Eb/No. For wimax communication used type of IEEE 802.16d with digital modulation 16 QAM and 64 QAM, include the variation of cylic prefix and bandwidth. Simulation test result show that simulation of SUI channel with type of modulation 16 QAM with cylic prefix 1/8, bandwidth 1.5MHz can repair almost entirety of performance SUI channel. Five SUI channel show best performance when at gyration of Eb/No 5dB up to 15 dB. While result of simulation SUI channel with type of modulation 16QAM with cylic prefix 1/16, bandwidth 20MHz showing bad performance, when improvement Eb/No of gyration BER between 10-1 dan 100 for channel SUI-2, SUI-3, SUI-4, SUI-5, SUI-6. Result of simulation SUI channel with type of modulation 64 QAM with cylic prefix 1/8, bandwidth 1.5MHz showing best performance. Result of simulation SUI channel with type of modulation 64 QAM with cylic prefix 1/16, bandwidth 20MHz showing bad performance. Keyword : 802.16d, SUI channel, WiMAX, cylic prefix, bandwidth.